Knee osteoarthritis pain and stretching exercises: a systematic review and meta-analysis. (March 2022) - Luan, Lijiang; El-Ansary, Doa; Adams, Roger; Wu, Sam; Han, Jia
Abstract: Objective: To evaluate the effectiveness of stretching exercises for pain relief in individuals with knee osteoarthritis (KOA). Data sources: Nine databases (PubMed, Embase, Cochrane Library, Web of Science, EBSCO, PEDro, CNKI, WanFang and CQVIP) were searched in December 2020. Study selection: Randomised controlled trials (RCTs) involving stretching exercises conducted on individuals with KOA were included. Study appraisal and synthesis methods: Literature quality and risk of bias were assessed with the Physiotherapy Evidence Database scale and Cochrane Collaboration tool, respectively. Data were extracted by two independent assessors using a standardised form. The weighted mean difference (WMD) and standard deviations (SD) with 95% confidence intervals (CI) were analysed. Results: In total, 373 studies were screened, with a final selection of 19 RCTs involving 1250 participants; of these, 18 RCTs were included in the final meta-analysis. When stretching exercises were used alone, the reduction of pain using a visual analogue scale was both significant and clinically meaningful (WMD 1.86; 95% CI 1.31 to 2.41). When stretching exercises were used in combination with other exercises, the pain reduction was still significant but its clinical significance became questionable (WMD 1.31; 95% CI 0.77 to 1.85). Limitations: The sample size of studies using stretching exercises alone was small, and some of the pooled studies were heterogeneous. Conclusions: Stretching exercises can be useful in pain management in individuals with KOA, especially when used alone. Programmes involving both stretching exercises and other exercises may improve function but may not achieve a clinically effective reduction in pain. Systematic review registration number Research Registry (No. reviewregistry813).